Exploring trends of running performance during matches of professional soccer players in Montenegro: A longitudinal study - Goranović, Kosta; Hadžić, Rašid; Petković, Jovica; Joksimović, Marko (Frontiers in Public Health, 2022)
The practical value of monitoring is that well-chosen performance indicators can help coaches identify the good and bad performance of individuals or teams. Match external monitoring is useful in establishing the physiological requirements of the sport and assessing how a certain player compares to the requirements of their event in this regard. The aim of the study was to analyze the trend component of running performance during the game of professional soccer fitness in Montenegro. The research included a sample of 82 professional soccer players. The first subsample included 44 professional soccer players of the football club Budućnost from Podgorica, height 185.89 ± 6.29 cm, mass 81.06 ± 5.47 kg, BMI 23.47 ± 0.96 kg/m2, age 28.86 ± 3.85 yrs. The second subsample included 38 professional soccer players from the Sutjeska football club from Nikšić, height 181.88 ± 6.35 cm, mass 77.28 ± 6.78 kg, BMI 23.32 ± 1.08 kg/m2, age 29.43 ± 5.68 yrs. The InStat kinematic system captured the outfield players using six cameras placed around the perimeter of the field at the minimal height of 12 m. The frame frequency was 25 frames per second where data was centralized for further analysis. Not find statistically significant differences were observed in this article p>.05. The results of the current research indicate that the soccer players who compete in Montenegro are below the values achieved by the soccer players who compete in Europe.